PENGISIAN SIGN IN DALAM MENINGKATKAN KEPATUHAN SAFE SURGERY DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA II - Andri Firman Saputra; Elsye Maria Rosa (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2015)
Background: Complications and deaths due to surgery become one of the global health problems. World Health Organization estimates that at least half a million deaths due to preventable surgical. An effort to improve the quality of surgical services including the Surgical Safety Checklist to use made by World Health Organization. Compliance to use this surgery checklist which is can increase the number of safe surgery,reduce the wrong site surgery and nearmiss. Method: This research is a qualitative action research design. The study population was all the doctors and nurse anesthetist. Number of samples 6 people. The data is collected by observation sheet Surgical Safety Checklist: Sign In RS PKU Muhammadiyah Yogyakarta Unit II for 3 cycles of observation. Result and Discussion: The results of observations on the first to the third cycle shows that all disobeying nurse anesthetist (100%) the Surgical Safety Checklist to fill: Sign In. The results of the response every cycle and a structured interview with the anesthesiologist showed that nurses are still confused how to use the checklist, the checklist has not been a necessity, the culture of patient safety is still minimal, lack quality of human resources, lack of supervision and lack of socialization mechanisms Surgical Safety Checklist noncompliance that influence nurses Sign In to to fill. Conclusion: Completing Sign In in the installation of surgery center in PKU Muhammadiyah Yogyakarta Unit II Hospital is noncompliance, because they still haven’t got the identity bracelet mounted on a patient who will be operating and marking the location of a rare surgery. Advice to hospital are to create a Standard Operating Procedure (SOP), SOP socialize regularly, make in-house training, increase the commitment of doctors and nurses, create a surveillance system, create a system of reward and punishment.